The 16-day planetary waves: multi-MF radar observations from the arctic to equator and comparisons with the HRDI measurements and the GSWM modelling results - Luo, Y.; Hall, Chris; Manson, A.H.; Meek, C.E.; Meyer, C.K.; Burrage, M.D.; Fritts, D.C.; Hocking, W.K.; MacDougall, J.; Riggin, D.M.; Vincent, R.A. (European Geophysical Society, 2002)
The mesospheric and lower thermospheric (MLT) winds (60–100 km) obtained by multiple MF radars, located from the arctic to equator at Tromsø (70° N, 19° E), Saskatoon (52° N, 107° W), London (43° N, 81° W), Hawaii (21° N, 157° W) and Christmas Island (2° N, 157° W), respectively, are used to study the planetary-scale 16-day waves. Based on the simultaneous observations (1993/1994), the variabilities of the wave amplitudes, periods and phases are derived. At mid- and high-latitude locations the 16-day waves are usually pervasive in the winter-centred seasons (October through March), with the amplitude gradually decreasing with height. From the subtropical location to the equator, the summer wave activities become strong at some particular altitude where the inter-hemisphere wave ducts possibly allow for the leakage of the wave from the other hemispheric winter. The observational results are in good agreement with the theoretical conclusion that, for slowly westward-traveling waves, such as the 16-day wave, vertical propagation is permitted only in an eastward background flow of moderate speed which is present in the winter hemisphere. The wave period also varies with height and time in a range of about 12–24 days. The wave latitudinal differences and the vertical structures are compared with the Global Scale Wave Model (GSWM) for the winter situation. Although their amplitude variations and profiles have a similar tendency, the discrepancies are considerable. For example, the maximum zonal amplitude occurs around 40° N for radar but 30° N for the model. The phase differences between sites due to the latitudinal effect are basically consistent with the model prediction of equatorward phase-propagation. The global 16-day waves at 95 km from the HRDI wind measurements during 1992 through 1995 are also displayed. Again, the wave is a winter dominant phenomenon with strong amplitude around the 40–60° latitude-band on both hemispheres.